Reforming pensions - Nicholas Barr; Peter Diamond (Center for Economic Studies and ifo Institute (CESifo), 2009)
This article, based on two books (2008, forthcoming), sets out principles for pension design: pension systems have multiple objectives, analysis should consider the pension system as a whole, analysis should be in a second-best context, different systems share risks differently and have different effects by generation and by gender. The article considers policy implications: there is no single best pension design; earlier retirement does not reduce unemployment; unsustainable pension promises should be addressed directly; adding funding in a PAYG mandatory system may or may not be welfare improving; and implementation matters design should not exceeds a country's capacity to implement.
Keywords: H55; 330; Pension; social security; Rentenreform; Rentenfinanzierung; Wirtschaftspolitisches Ziel; Second Best